ANALISIS PEMEROLEHAN BAHASA PADA ANAK USIA 1 TAHUN 6 BULAN DARI SEGI SINTAKSIS - Susi Susanti; Annindy Ayang Rahmasandy; Enjang Supriatna; Rosi Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study is a preliminary study to see the acquisition of children’s language in terms of syntax. The subject of the study was a native child of Sundanese language from Cilesang Bandung area. The data used for the analysis of this research is authentic data that is incised through audio recording. The data can be analyzed with three main features of the syntax aspects of paragraph length, sintactic structure and the number of speeches. The minimum Length of Utterance (MLU) estimation following Brown’s Stages of Development is used to determine the stage of development of children. From the analysis conducted in this study it can be seen that Fahlevi has MLU 1,21 which means being in phase II that is at the age should be. Based on research Fahlevi has been able to speak from one words which means Fahlevi has been able to tell the full sentence in his age.